Replication Data for: Healthy and sustainable diets from today to 2050 – the role of international trade - Mapes, Brendan Robert; Prager, Steven D.; Béné, Christophe; González Rodriguez, Carlos Eduardo (2022)
Projection data – dietary quality indices modeled according to EAT-Lancet dietary guidelines. Produced in the study “Mapes B, Prager SD, Béné C, Gonzalez CE. Healthy and sustainable diets from today to 2050 – the role of international trade. PLOS ONE. 2021;”.